Analisis Faktor Pemicu Selisih Anggaran Dan Realisasi Pendapatan Pada Kementerian Keuangan - Hamidah, Maya (Politeknik Bisnis Indonesia, 2024)
This study analyzed the trigger factors for budget differences and revenue realization in the Ministry of Finance in 2023. The Ministry of Finance plays an important role in the management of finance and the realization of state revenues. The goal of this analysis explains the factors that trigger the difference between the budget that has been set and the realization of income in the Ministry of Finance. The method used in this analysis is quantitative descriptive in analyzing financial data relevant to the Ministry of Finance. The data used in this analysis are the Annual Financial Report and APBN published by the Ministry of Finance. Analysis of budget differences and realization of revenue in the Ministry of Finance in 2023 showed mixed results in various revenue posts. Domestic tax revenues are realized at 102.16% of the budget, positive indicators such as economic stability and mining sector contributions, although they still face challenges in certain sectors. International trade tax revenues only reached 88.47% of the budget due to a decrease in import value and fluctuations in commodity prices. For Non-Tax State Revenue, the General Service Agency's revenue reached 106.94% of the target due to improved banking services and education fund management, as well as the realization of other non-tax revenue even exceeded 160% of the target due to good financial management, interest income, and fines.